PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH DENGAN MENGGUNAKAN MODEL ROLE PLAYING DI SEKOLAH DASAR - Marshella Septi Zulefni; Fadhilaturrahmi; Mufarizuddin; Sumianto; Yenni Fitra Surya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low problem-solving ability of fifth-grade students at UPT SDN 016 Bukit Ranah. This study aims to improve students' problem-solving abilities by using the Role playing model. This study uses the Classroom Action Research (CAR) method which consists of two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation, and reflection. The research time was carried out in July 2025. The subjects of this study were 16 fifth-grade students of UPT SDN 016 Bukit Ranah consisting of 3 boys and 6 girls. Data collection techniques were in the form of observation and documentation. The results of the study indicate that using the Role playing model can improve students' problem-solving abilities. This is shown before the study, students' problem-solving abilities were 25%, then in cycle I meeting I increased to 43.75%, cycle 1 meeting II increased to 56.25%. Furthermore, in cycle II meeting I increased to 68.75%, and cycle II meeting II increased to 87.5%. Thus, it can be concluded that using the role-playing model can improve students' problem-solving skills at the UPT SD Negeri 016 Bukit Ranah.